(untitled) (Public Sector Economics - submission site, 2021)
This paper provides an overview of different inheritance tax regimes in selected European countries and the United States. We show that in the majority of countries the tax rate is related to the relationship between testator and the beneficiary as well as the value of the inherited assets. In most countries the transfer of wealth within families is treated preferentially (lower tax rates, tax exemptions and reliefs). This is particularly the case for business assets and family homes. The analysis further discusses the features and effects of inheritance tax regimes, which include behavioural responses of individuals and different distributional effects of an inheritance tax. Although the actual revenues of inheritance taxation are quite low in the selected countries, some indicators point to higher revenue potentials in the future. An appropriate design for inheritance taxation could further help to decelerate the increase in wealth inequality.